2021
DOI: 10.3390/su13116289
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Organically Grown Compared to Conventionally Grown Potato and the Processed Products: A Review

Abstract: Interest in organic foods is increasing at a moment when humanity is facing a range of health challenges including the concern that some conventionally produced foods may pose possible adverse effects on human and livestock health. With the increasing human population, intensive production is increasingly trending towards high-input systems that aim to close yield gaps, increase crop yields, and develop new crop varieties with higher yield potential and tolerance to biotic and abiotic stresses, all within the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 204 publications
(295 reference statements)
3
7
0
Order By: Relevance
“…In this respect, addition of animal compost significantly recorded the higher values of average fruit weight and total yield than the plant compost, while number of fruit recorded no significant effect. These results are in concurrence with (Abou El Goud, 2020;Djaman et al, 2021) they observed that the organic fertilizers are valuable for plants because of their beneficial impact on the chemical, physical, and microbial traits of the soil, also they found that animal compost produced in root zone high amount of IAA which in turns, reciprocally growth and increase plant production. Besides that, they focused on the organic agricultural production in Egypt in order to avoid plant and environmental pollution with various elements and to diminish the utilization of chemical fertilizers (Shaheen et al 2018;Djaman et al 2021).…”
Section: Yield and Its Componentssupporting
confidence: 83%
See 2 more Smart Citations
“…In this respect, addition of animal compost significantly recorded the higher values of average fruit weight and total yield than the plant compost, while number of fruit recorded no significant effect. These results are in concurrence with (Abou El Goud, 2020;Djaman et al, 2021) they observed that the organic fertilizers are valuable for plants because of their beneficial impact on the chemical, physical, and microbial traits of the soil, also they found that animal compost produced in root zone high amount of IAA which in turns, reciprocally growth and increase plant production. Besides that, they focused on the organic agricultural production in Egypt in order to avoid plant and environmental pollution with various elements and to diminish the utilization of chemical fertilizers (Shaheen et al 2018;Djaman et al 2021).…”
Section: Yield and Its Componentssupporting
confidence: 83%
“…These results are in concurrence with (Abou El Goud, 2020;Djaman et al, 2021) they observed that the organic fertilizers are valuable for plants because of their beneficial impact on the chemical, physical, and microbial traits of the soil, also they found that animal compost produced in root zone high amount of IAA which in turns, reciprocally growth and increase plant production. Besides that, they focused on the organic agricultural production in Egypt in order to avoid plant and environmental pollution with various elements and to diminish the utilization of chemical fertilizers (Shaheen et al 2018;Djaman et al 2021). 5), in the most cases of the foliar applications exhibited high significant increases of yield components included average fruit weight and total yield, while number of fruit had no significant effect in the two tested seasons compared to control treatment.…”
Section: Yield and Its Componentssupporting
confidence: 83%
See 1 more Smart Citation
“…Organic foods are often perceived as being healthier and having be er flavor than conventionally grown crops, as conventional farming practices are usually associated with unwanted residues from pesticides and herbicides. These may accumulate in the soil and in certain crops, such as potato tubers, and therefore, negatively impact organoleptic properties as well as human and animal health [17]. Higher concentrations of nitrates and lutein were found in conventionally farmed potato tubers when compared to organic potato tubers [14].…”
Section: Organic Farmingmentioning
confidence: 99%
“…Due to environmental biotic and abiotic stresses, organic plant management involves higher bioactive compound synthesis in plants [ 34 , 35 , 36 ]. This leads to higher concentrations of antioxidants in fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%